Beyond the essay film : subjectivity, textuality and technology - Vassilieva, Julia; Williams, Deane (Amsterdam : Amsterdam University Press, 2020)
In the wake of the explosion in the production of essay films over the last twenty-five years and its subsequent theorization in scholarly literature, this volume seeks to historicize these intertwined developments within the 'long duree' of the twentieth century and into the twenty-first. 'Beyond the Essay Film' seeks to not only acknowledge the influential predecessors of this - in the view of many critics - most interesting type of contemporary filmmaking - but also to speculate about its possible transformation as we move forward into the uncharted waters of the twenty-first - digital - century. Focusing on three specific axes that underpin and shape the articulation of the essay film as a specific cultural form - subjectivity, textuality and technology - this book explores how changes along and across these dimensions affect historical shifts within essay film practice and its relation to other types of cinema and neighbouring art forms.
Enthält bibliografische Angaben und Index.
boek
Keywords: Documentary films; Experimental films; Criticism, interpretation, etc